ANALISIS FAKTOR PENGALAMAN IBU PADA 1000 HPK DENGAN KEJADIAN STUNTING DIWILAYAH KERJA PUSKESMAS GARUDA KOTA PEKANBARU - Winda Septiani; Nurhapipa Nurhapipa; Felianda Kartilian; Trimbi Febri Sapta; Nisa Meilani (Ensiklopedia of Journal, 2023)
Stunting is a condition of growth failure of children under five years old (infants under five years old) which results in children being too short for their age which is the result of chronic malnutrition. Factors causing stunting children in Pekanbaru City based on data from the Pekanbaru City Health Office in 2019 are caused by several factors including; social factors such as the way of feeding children, insufficient family economic factors, and infection factors in children, where there is a significant relationship between the history of infectious diseases that children have suffered and the incidence of stunting in children under five. This type of research is a combined method (qualitative and quantitative) using a 2-stage research method, namely a qualitative research method with a descriptive research type and an analytical quantitative research method with a Cross Sectional design type which was carried out at the Garuda Health Center from February to October 2022 with a total sample of 100 children under five and purposive sampling of samples. Data collection using interview guidelines, questionnaires. Based on research on the frequency of events of having stunted toddlers, namely 29% and multivariate analysis with multiple logistic regression tests, prediction factors concluded that parenting (p value = 0.000) is an independent variable that is significantly related to the risk of having a stunted toddler and a confounding variable on the risk of having a stunted toddler, namely parenting and maternal knowledge. For puskesmas, it is hoped that it can provide information related to stunting problems at the Garuda Health Center in Pekanbaru City in 2022 by collaborating across programs in the puskesmas for health workers on duty at: KIA Poly, Nutrition Poly, and Promkes Poly.